Biogeography of a neotropical songbird radiation reveals similar diversification dynamics between montane and lowland clades. (5th May 2022) - Buainain, Nelson; Ferreira, Mateus; Avendaño, Jorge E.; Cadena, Carlos D.; Faircloth, Brant C.; Brumfield, Robb T.; Cracraft, Joel; Ribas, Camila C.
Abstract: Aim: Continental evolutionary radiations provide opportunities to understand how landscape evolution and biotic factors interact to generate species diversity. Additionally, understanding whether diversification dynamics differ between montane and lowland environments is a long‐standing question with few comparative analyses in the Neotropics. To address these questions, we investigated the biogeographical patterns and the evolutionary processes underlying the diversification of a songbird genus, and compared diversification dynamics of clades occurring in lowland and montane Neotropical habitats. Location: Neotropical montane and lowland forests. Taxon: Arremon (Aves: Passerellidae). Methods: We sequenced genomic data (ultra‐conserved elements, UCEs) of 92 individuals (including historical skin specimens) comprising 47 of 50 currently recognized subspecies in the genus and collected habitat association data to (1) build the most complete phylogenetic hypothesis for the genus to date using maximum likelihood and Bayesian methods with a concatenated matrix, and a multi‐species coalescent method based on quartets; and (2) reconstruct the evolution of their ancestral ranges, habitat association and diversification rates. Results: All phylogenetic methods recovered essentially the same topology with strong support values for most interspecific nodes revealing relationships among species. We found evidence for a montane and humid ancestral range in Central America in the late Miocene and a later expansion into the lowlands of Central America, as well as into the lowlands and mountains of South America. Despite some temporal variation in diversification rate, we found overall similar diversification dynamics between montane and lowland clades. Main conclusion: Species diversity within the genus is likely underestimated by the current taxonomic arrangement. The colonization of lowlands and dry forests, and expansion across South America, may have provided new geographical and ecological opportunities for speciation resulting in high species diversification. Overall diversification dynamics were comparable between montane and lowland clades, contrasting with previous studies focused on such comparisons for Neotropical birds.